Pemanfaatan Limbah Botol Plastik Sebagai Media Tanaman Hidroponik Kangkung Di SD Negeri Gunung Anyar 273 - Ida Wahyu Romandani; Tessa Oktaviani Dahlan; Nuriah Yuliati; Nisa Hafi Idhoh Fitriana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Waste is unused material that comes from humans, animals and plants in solid, liquid or gas form. The problem of plastik waste is a common phenomenon in Indonesia that needs to find a solution. This can be done by utilizing plastik waste for appropriate technology such as using plastik bottle waste to be used as a medium for hydroponic water spinach plants. This activity was carried out at SD Negeri Gunung Anyar 273 with the aim of increasing students' knowledge regarding hydroponic water spinach plants and the use of plastik bottle waste as a medium for hydroponic water spinach plants, as well as reducing plastik waste found in the school environment. The methods used in this activity are lectures and direct practice in the field which consists of various stages, namely field survey, counseling, joint practice, and plant monitoring. The result of this activity is that students can make hydroponic water spinach plant media from plastik bottle waste and also have a good understanding of caring for hydroponic plants.